Distribution of Turkish Helophorus fabricius, 1775 (Coleoptera, Helophoridae) II. Subgenus Atracthelophorus, with two new records and some ecological notes - Incekara, Ümit; Mart, Abdullah; Erman, Orhan (My University, 2005)
Two newly recorded Helophorus Fabricius, 1775 species/subspecies for the Turkish fauna, Helophorus (Atracthelophorus) shatrovskyi Angus, 1985 and H. (A.) leontis dixoni Angus, 1987, are compared against Turkish specimens (private collection). A list of subgenus Atracthelophorus species known from Turkey and their distribution in Turkey and worldwide is presented. The ecology of each examined species is discussed. © Tübi?tak.
Keywords: Coleoptera; Distribution; Helophoridae; Helophorus; Turkey